EXPLORING THE INFLUENCE OF UNIVERSITY-SME COLLABORATIVE INNOVATIONS ON TECHNOLOGY IN INDONESIA: A MULTILEVEL PERSPECTIVE - Budi Raharja , Arif; Ruchiyat, Endang; Matriadi , Faisal (KRIEZ ACADEMY : Journal of development and community service, 2024)
Technological innovation plays a key role in facing the complex challenges faced by Indonesia in the era of globalization. Collaboration between universities and Small and Medium Enterprises (UKM) has been recognized as an effective way to accelerate technological development that is relevant to society's needs. In this study, we explore the influence of collaborative innovation between universities and SMEs on technology in Indonesia using a multilevel perspective. This perspective includes three levels of analysis: micro, mezzo, and macro. At the micro level, we see the interaction of individuals and organizations in collaboration. At the mezzo level, we consider the dynamics and relationships between universities and SMEs. Meanwhile, at the macro level, we pay attention to external factors such as government policies and economic conditions that influence collaboration. Through this analysis, we highlight the important role of government policy in creating a conducive environment for collaboration, supporting necessary infrastructure, regulatory and bureaucratic reform, determining strategic research priorities, and establishing innovation networks. We conclude that collaboration between universities and SMEs has great potential to accelerate technological development in Indonesia, but requires appropriate support and policies from the government as well as good coordination between various stakeholders.